Treatment algorithm for metastatic renal cell carcinoma–recommendations based on evidence and clinical practice - Bergmann, Lothar; Beck, Jochaim; Bothe, Kathrin; Brinkmann, Olaf A.; Buse, Stephan; Goebell, Peter; Gruenwald, Viktor; Holzapfel, Konstantin; Kuebler, Hubert; Marschner, Norbert W.; Mickischk, Gerald; Schultze-Seemann, Wolfgang; et al. (Oncology research and treatment, 2014)
Until a few years ago, the treatment options for metastatic renal cell cancer (mRCC) were very limited. The growing understanding of the molecular pathomechanisms underlying RCC allowed the development of new treatment approaches. Meanwhile, several approved target-oriented substances from different drug classes are available for mRCC. The mechanism of action of vascular endothelial growth factor (VEGF) and VEGF receptor or mTOR inhibition is well documented by phase III trials and reflected in the current guidelines. However, no predictive biomarkers have been identified in mRCC so far to demonstrate a benefit by a specific compound in an individual patient. Meanwhile, the sequential use of 'targeted therapies' in mRCC has been established as standard treatment. The optimal sequence of available agents is still unclear. A German RCC expert panel discussed and developed an algorithm for the choices of first- and second-line treatment in mRCC based on established clinical criteria.
EVALuna2:16301